Strengthening The Checks and Balances System in The Constitutional Structure After The Amendments to The 1945 Constitution - Akbar Rizqo; Fenita Lara Bheta; M. Roslan Mohd Nor; Afrizal Adi Saputra (Fakultas Syariah dan Hukum UIN Raden Fatah Palembang, 2026)
This study analyzes the strengthening of the checks and balances system within Indonesia’s constitutional structure after the amendments to the 1945 Constitution. The research focuses on the imbalance of authority among state institutions, particularly the expansion of executive influence over the legislative process and the limited effectiveness of institutional oversight mechanisms. These conditions indicate a legal gap in the practical implementation of checks and balances despite formal constitutional arrangements. This study employs normative legal research with statutory and conceptual approaches, using primary, secondary, and tertiary legal materials obtained through literature review. The findings show that although constitutional amendments have clarified the distribution of powers among the legislative, executive, and judicial branches, challenges persist in the form of overlapping authorities, weak supervisory functions, and political intervention in institutional relations. The role of the Constitutional Court has been significant in maintaining constitutional supremacy; however, its authority has not fully addressed systemic imbalances. This study offers a conceptual contribution by emphasizing the need to strengthen institutional oversight, refine the separation of powers, and develop a constitutional culture to ensure a more effective checks and balances system in Indonesia.